The Impact of Perceived Organizational Support and Social Support on Employee Performance: The Mediating Role of Organizational Commitment - Laode Asfahyadin Aliddin; Dedy Takdir Syaifuddin; Yusuf Montundu; Siti Marlina (Universitas Hayam Wuruk Perbanas, 2024)
The aim of this research is to assess and elucidate the impact of perceived organizational support and social support on employee performance, with organizational commitment serving as a mediating factor. The study involved 543 employees from the Regional Secretariat Office of Southeast Sulawesi Province. A sample of 84 employees was selected using a proportional cluster random sampling technique. Data were collected through questionnaires and interviews. For statistical analysis, SmartPLS 4.0 software was employed to model structural equations. The findings reveal that perceived organizational support, social support, and organizational commitment all influence employee performance. Specifically, perceived organizational support does not significantly affect organizational commitment, whereas social support has a significant impact on it. Organizational commitment does not mediate the relationship between perceived organizational support and employee performance; however, it does mediate the relationship between social support and employee performance. The Regional Secretariat Office of Southeast Sulawesi Province and related stakeholders can utilize these findings to enhance employee performance by focusing on employee commitment, perceived organizational support, and social support.